A covalent organic framework material containing trifluoromethyl groups in the pores, a preparation method and its application in the adsorption and separation of small molecule hydrocarbons

The performance of existing covalent organic framework materials in small molecule alkane adsorption and separation applications is solved by using TPCOF-CF3 materials synthesized by 2,5-diaminotrifluorotoluene and 2,4,6-triformylphenylglycopylol. The problem of insufficient results has achieved efficient adsorption and separation effects.

CN115873193BActive Publication Date: 2025-02-07JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211529303.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-02-07
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The existing covalent organic framework materials have problems with insufficient performance in small molecule alkane adsorption and separation applications, especially lack of effective technical means in the regulation of the channel size and structure.

Method used

Using 2,5-diaminotrifluorotoluene and 2,4,6-triformylphenylglycopyl as monomers, the Schiff base formation reaction catalyzed by acetic acid is used to synthesize the pores containing trifluoromethyl under various reaction conditions. TPCOF-CF3, a covalent organic framework material.

Benefits of technology

The prepared TPCOF-CF3 material exhibits good crystallinity, high specific surface area and high stability, which significantly improves the adsorption and separation of small molecule alkanes, especially in the adsorption and separation of methane, ethane and propane. Effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115873193B_ABST
    Figure CN115873193B_ABST
Patent Text Reader

Abstract

A covalent organic framework material with trifluoromethyl in the pores, a preparation method and its application in the adsorption and separation of small molecule hydrocarbons, belonging to the technical field of porous organic material preparation. The present invention uses 2,5-diaminotrifluorotoluene and 2,4,6-triformylpyrogallol as monomers, uses acetic acid solution as a catalyst, introduces trifluoromethyl to regulate the structure and performance of the product, and prepares the covalent organic framework material TPCOF-CF3 by regulating the reaction solvent and ratio, the amount of acetic acid and the activation solvent. Tests show that the BET specific surface area of ​​TPCOF-CF3-8 is 825m 2 g ‑1 The pore size distribution is mainly 1.5 nm micropores; at 298 K and 1 bar, the adsorption capacities of methane, ethane, and propane for TPCOF‑CF3‑8 are 4.8, 30, and 63 cm 3 g ‑1 , the separation ratios of propane / methane and ethane / methane are 346.3 and 13.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of porous organic material preparation, and specifically relates to a covalent organic framework material (TPCOF-CF3, COF=Covalent Organic Framework) containing trifluoromethyl in the pores, which is synthesized under various reaction conditions using 2,5-diaminotrifluorotoluene and 2,4,6-triformylpyrogallol as monomers and acetic acid as a catalyst, and its application in the adsorption and separation of small molecule alkanes. Background Art

[0002] In 2005, OM Yaghi et al. first reported (Science, 2005, 310: 1166-1170) crystalline COF-1 and COF-5. COFs are crystalline two-dimensional or three-dimensional porous polymers formed by covalent bonds formed by polymerization of organic molecular building blocks. The composition and structure of COFs determine that they have good crystallinity, high specific surface area, permanent porosity and high stability. At present, COFs have shown good application potential in the fields of gas adsorption and separation, sensing and catalysis. In the polymerization reaction of preparing COFs, the Schiff base reaction between aldehydes and amines is very efficient and typical. When synthesizing COFs, functional groups are introduced on the organic building blocks to regulate the structure and properties of COFs. The introduction of functional groups can modify the pore wall structure and adjust the pore size. In this patent application, 2,5-diaminotrifluorotoluene and 2,4,6-triformylpyrogallol are used as monomers, and the structure and properties of the material are regulated by introducing trifluoromethyl. Summary of the invention

[0003] The present invention aims to provide a covalent organic framework material (TPCOF-CF3, COF=Covalent Organic Framework) containing trifluoromethyl groups in its pores and its application in the adsorption and separation of small molecule alkanes (methane, ethane and propane).

[0004] The reaction monomers of the present invention are 2,5-diaminotrifluorotoluene and 2,4,6-triformylpyrogallol (the reaction monomers contain trifluoromethyl), the reaction catalyst is acetic acid solution of different concentrations, the reaction solvent is a two-component mixed solvent, and the structural formulas of 2,5-diaminotrifluorotoluene and 2,4,6-triformylpyrogallol are as follows:

[0005]

[0006] The method for preparing a covalent organic framework material containing trifluoromethyl groups in the pores of the present invention comprises the following steps:

[0007] (1) Weigh 2,4,6-triformylpyrogallol (42 mg, 0.2 mmol) and 2,5-diaminotrifluorotoluene (52.8 mg, 0.3 mmol) and add them to a reaction container, then add a two-component mixed solvent with a total volume of 2 mL, and ultrasonicate for 50 to 70 minutes to ensure that the solution is evenly mixed; the two-component mixed solvent is a mixture of o-dichlorobenzene and n-butanol or 1,4-dioxane and mesitylene; the volume ratio of o-dichlorobenzene to n-butanol or 1,4-dioxane to mesitylene is 1:0.2 to 5;

[0008] (2) adding 0.1 to 0.5 mL of 3 to 12 M acetic acid solution to the solution of step (1), allowing to stand for 20 to 40 minutes, and then performing a "freeze-vacuum-thaw" cycle operation 2 to 5 times in a liquid nitrogen and argon atmosphere, with the freezing temperature being 77 K, and thawing to room temperature; then sealing the reaction vessel under vacuum and reacting at 110 to 130° C. for 60 to 80 hours;

[0009] (3) After cooling the reaction container to room temperature, slowly open it and vacuum filter to obtain a solid; wash the obtained solid with anhydrous tetrahydrofuran, anhydrous acetone or anhydrous methanol solvent and soak it for 20 to 30 hours, during which the solvent is changed every 6 to 8 hours; finally, vacuum dry the obtained solid at 90 to 110° C. for 10 to 15 hours, thereby obtaining the covalent organic framework material containing trifluoromethyl in the pores of the present invention.

[0010] When preparing TPCOF-CF3 in the present invention, the polymerization reaction is a Schiff base formation reaction catalyzed by acetic acid. When using the Schiff base reaction to prepare COFs materials, the main influencing factors include the type and amount of solvent, the type and amount of catalyst acid, the activation solvent, the reaction temperature and reaction time, etc. The preparation reaction equation is as follows:

[0011]

[0012] The covalent organic framework material containing trifluoromethyl in the pores prepared by the present invention has a structure as shown below:

[0013] BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 : Powder diffraction spectrum of TPCOF-CF3 synthesized in 3M acetic acid of the present invention (curve 1 is TPCOF-CF3-4; curve 2 is TPCOF-CF3-1; curve 3 is TPCOF-CF3-3; curve 4 is TPCOF-CF3-5; curve 5 is TPCOF-CF3-2);

[0015] Figure 2: Powder diffraction spectrum of TPCOF-CF3 synthesized in 6M acetic acid of the present invention (curve 1 is TPCOF-CF3-8; curve 2 is TPCOF-CF3-7; curve 3 is TPCOF-CF3-6; curve 4 is TPCOF-CF3-9; curve 5 is TPCOF-CF3-10);

[0016] Figure 3 : Powder diffraction spectrum of TPCOF-CF3 synthesized in 9M acetic acid of the present invention (curve 1 is TPCOF-CF3-13; curve 2 is TPCOF-CF3-11; curve 3 is TPCOF-CF3-15; curve 4 is TPCOF-CF3-12; curve 5 is TPCOF-CF3-14);

[0017] Figure 4 : Powder diffraction spectrum of TPCOF-CF3 synthesized in 12M acetic acid of the present invention (curve 1 is TPCOF-CF3-18; curve 2 is TPCOF-CF3-16; curve 3 is TPCOF-CF3-20; curve 4 is TPCOF-CF3-17; curve 5 is TPCOF-CF3-19);

[0018] Figure 5 : Powder diffraction patterns of 4 materials with good crystallinity under different acid concentrations and volumes of TPCOF-CF3 synthesized by the present invention (curve 1 is TPCOF-CF3-8, curve 2 is TPCOF-CF3-13, curve 3 is TPCOF-CF3-18, and curve 4 is TPCOF-CF3-4);

[0019] Figure 6 : Powder diffraction patterns corresponding to TPCOF-CF3 synthesized in different solvent systems (curve 1 is TPCOF-CF3-8; curve 2 is TPCOF-CF3-21);

[0020] Figure 7 : Powder diffraction patterns corresponding to TPCOF-CF3 synthesized under different solvent ratios (curve 1 is TPCOF-CF3-8; curve 2 is TPCOF-CF3-25; curve 3 is TPCOF-CF3-26; curve 4 is TPCOF-CF3-27; curve 5 is TPCOF-CF3-28; curve 6 is TPCOF-CF3-24; curve 7 is TPCOF-CF3-29; curve 8 is TPCOF-CF3-23; curve 9 is TPCOF-CF3-22);

[0021] Figure 8 : Powder diffraction patterns corresponding to TPCOF-CF3 synthesized under different activation solvents (curve 1 is ultra-dry tetrahydrofuran; curve 2 is anhydrous acetone; curve 3 is anhydrous methanol);

[0022] Fig. 9 : Infrared spectrum of TPCOF-CF3 synthesized by the present invention under 3M acetic acid (curve 1 is TPCOF-CF3-5; curve 2 is TPCOF-CF3-4; curve 3 is TPCOF-CF3-3; curve 4 is TPCOF-CF3-2; curve 5 is TPCOF-CF3-1; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol);

[0023] Fig.10 : Infrared spectrum of TPCOF-CF3 synthesized by the present invention under 6M acetic acid (curve 1 is TPCOF-CF3-10; curve 2 is TPCOF-CF3-9; curve 3 is TPCOF-CF3-8; curve 4 is TPCOF-CF3-7; curve 5 is TPCOF-CF3-6; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol);

[0024] Fig.11 : Infrared spectrum of TPCOF-CF3 synthesized in 9M acetic acid of the present invention (curve 1 is TPCOF-CF3-15; curve 2 is TPCOF-CF3-14; curve 3 is TPCOF-CF3-13; curve 4 is TPCOF-CF3-12; curve 5 is TPCOF-CF3-11; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol);

[0025] Fig.12 : Infrared spectrum of TPCOF-CF3 synthesized by the present invention under 12M acetic acid (curve 1 is TPCOF-CF3-20; curve 2 is TPCOF-CF3-19; curve 3 is TPCOF-CF3-18; curve 4 is TPCOF-CF3-17; curve 5 is TPCOF-CF3-16; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol);

[0026] Fig.13 : The powder diffraction spectrum corresponding to TPCOF-CF3-8 synthesized by the present invention;

[0027] Fig.14 : Thermogravimetric diagram corresponding to TPCOF-CF3-8 synthesized in the present invention;

[0028] Fig.15 : Nitrogen adsorption-desorption isotherm corresponding to TPCOF-CF3-8 synthesized in the present invention;

[0029] Fig.16: The pore size distribution diagram corresponding to the TPCOF-CF3-8 synthesized in the present invention;

[0030] Fig.17 : The scanning electron microscope image corresponding to the TPCOF-CF3-8 synthesized by the present invention;

[0031] Fig.18 : The nuclear magnetic carbon spectrum corresponding to TPCOF-CF3-8 synthesized by the present invention;

[0032] Fig.19 : The adsorption isotherms of methane, ethane and propane of TPCOF-CF3-8 synthesized in the present invention at 298K;

[0033] Fig. 20 : The adsorption isotherms of methane, ethane and propane of TPCOF-CF3-8 synthesized in the present invention at 273K;

[0034] Fig.21 : Separation ratio curves of propane / methane (curve 1) and ethane / methane (curve 2) of TPCOF-CF3-8 synthesized in the present invention at 298K;

[0035] Fig. 22 : Separation ratio curves of propane / methane (curve 1) and ethane / methane (curve 2) of TPCOF-CF3-8 synthesized in the present invention at 273K;

[0036] Fig.23 : The powder diffraction spectrum corresponding to TPCOF-CF3-19 synthesized by the present invention;

[0037] Fig.24 : Nitrogen adsorption-desorption isotherm corresponding to TPCOF-CF3-19 synthesized in the present invention;

[0038] Fig.25 : The pore size distribution diagram corresponding to the TPCOF-CF3-19 synthesized in the present invention.

[0039] Figure 1 As shown, it is the powder diffraction spectrum of TPCOF-CF3 synthesized in 3M acetic acid of the present invention ((curve 1 is TPCOF-CF3-4; curve 2 is TPCOF-CF3-1; curve 3 is TPCOF-CF3-3; curve 4 is TPCOF-CF3-5; curve 5 is TPCOF-CF3-2), there is an obvious diffraction peak at about 5°, which proves that the crystallinity of the polymer is good and it is a long-range ordered crystalline porous material; in this group of experiments, 0.4mL of 3M acetic acid has the best crystallinity (TPCOF-CF3-4);

[0040] Figure 2As shown, it is the powder diffraction spectrum of TPCOF-CF3 synthesized in 6M acetic acid of the present invention (curve 1 is TPCOF-CF3-8; curve 2 is TPCOF-CF3-7; curve 3 is TPCOF-CF3-6; curve 4 is TPCOF-CF3-9; curve 5 is TPCOF-CF3-10), and there is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material; in this group of experiments, 0.3mL of 6M acetic acid has the best crystallinity (TPCOF-CF3-8);

[0041] Figure 3 As shown, it is the powder diffraction spectrum of TPCOF-CF3 synthesized in 9M acetic acid of the present invention (curve 1 is TPCOF-CF3-13; curve 2 is TPCOF-CF3-11; curve 3 is TPCOF-CF3-15; curve 4 is TPCOF-CF3-12; curve 5 is TPCOF-CF3-14), and there is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material; in this group of experiments, 0.3mL of 9M acetic acid has the best crystallinity (TPCOF-CF3-13);

[0042] Figure 4 As shown, the powder diffraction spectrum of TPCOF-CF3 synthesized in 12M acetic acid of the present invention is shown in curve 1 for TPCOF-CF3-18; curve 2 for TPCOF-CF3-16; curve 3 for TPCOF-CF3-20; curve 4 for TPCOF-CF3-17; and curve 5 for TPCOF-CF3-19). There is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material; in this group of experiments, 0.3mL of 12M acetic acid has the best crystallinity (TPCOF-CF3-18);

[0043] Figure 5 As shown, it is the powder diffraction pattern of 4 materials with good crystallinity of TPCOF-CF3 synthesized by the present invention at different acid concentrations and volumes (curve 1 is TPCOF-CF3-8, curve 2 is TPCOF-CF3-13, curve 3 is TPCOF-CF3-18, and curve 4 is TPCOF-CF3-4; among them, TPCOF-CF3-8 has the best crystallinity;

[0044] Figure 6As shown, the corresponding powder diffraction patterns of TPCOF-CF3 synthesized in different solvent systems (curve 1 is TPCOF-CF3-8, curve 2 is TPCOF-CF3-21), there is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material; in this group of experiments, when a binary mixed solvent of o-dichlorobenzene and n-butanol is used, TPCOF-CF3-8 has good crystallinity;

[0045] Figure 7 As shown, the powder diffraction patterns corresponding to TPCOF-CF3 synthesized under different solvent ratios (curve 1 is TPCOF-CF3-8; curve 2 is TPCOF-CF3-25; curve 3 is TPCOF-CF3-26; curve 4 is TPCOF-CF3-27; curve 5 is TPCOF-CF3-28; curve 6 is TPCOF-CF3-24; curve 7 is TPCOF-CF3-29; curve 8 is TPCOF-CF3-23; curve 9 is TPCOF-CF3-22) have obvious diffraction peaks at about 5°, proving that the polymer has good crystallinity and is a long-range ordered crystalline porous material; in this group of experiments, when the volume ratio of o-dichlorobenzene to n-butanol is 1:1, the obtained material TPCOF-CF3-8 has good crystallinity; it also shows that the use of other solvent ratios can also obtain products with the properties described in the present invention, but compared with the solvent volume ratio of 1:1, the crystallinity of the obtained material is reduced;

[0046] Figure 8 As shown, the corresponding powder diffraction patterns of TPCOF-CF3 synthesized in different activation solvents (curve 1 is ultra-dry tetrahydrofuran; curve 2 is anhydrous acetone; curve 3 is anhydrous methanol), there is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material; in this group of experiments, when ultra-dry tetrahydrofuran is used for activation, the crystallinity is good; using anhydrous acetone or anhydrous methanol as the activation solvent, the crystallinity of the obtained material is reduced compared with ultra-dry tetrahydrofuran;

[0047] Fig. 9 As shown, it is the infrared spectrum of TPCOF-CF3 synthesized in 3M acetic acid of the present invention (curve 1 is TPCOF-CF3-5; curve 2 is TPCOF-CF3-4; curve 3 is TPCOF-CF3-3; curve 4 is TPCOF-CF3-2; curve 5 is TPCOF-CF3-1; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol). At 3100-3500cm -1 The peak at 1642 cm is the characteristic absorption peak of -NH2 in 2,5-diaminotrifluorotoluene; -1The peak at the position is the characteristic absorption peak of -CHO in 2,4,6-triformylpyrogallol. After the polymerization reaction, the disappearance of the characteristic absorption peaks of -NH2 and -CHO of the corresponding monomers proves that the polymerization reaction is very thorough;

[0048] Fig.10 As shown, it is the infrared spectrum of TPCOF-CF3 synthesized in 6M acetic acid of the present invention (curve 1 is TPCOF-CF3-10; curve 2 is TPCOF-CF3-9; curve 3 is TPCOF-CF3-8; curve 4 is TPCOF-CF3-7; curve 5 is TPCOF-CF3-6; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol). At 3100-3500cm -1 The peak at position is the characteristic absorption peak of -NH2 in 2,5-diaminotrifluorotoluene, 1642 cm -1 The peak at the position is the characteristic absorption peak of -CHO in 2,4,6-triformylpyrogallol. After the polymerization reaction, the disappearance of the characteristic absorption peaks of -NH2 and -CHO of the corresponding monomers proves that the polymerization reaction is very thorough;

[0049] Fig.11 As shown, it is the infrared spectrum of TPCOF-CF3 synthesized in 9M acetic acid of the present invention (curve 1 is TPCOF-CF3-15; curve 2 is TPCOF-CF3-14; curve 3 is TPCOF-CF3-13; curve 4 is TPCOF-CF3-12; curve 5 is TPCOF-CF3-11; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol). At 3100-3500cm -1 The peak at position is the characteristic absorption peak of -NH2 in 2,5-diaminotrifluorotoluene, 1642 cm -1 The peak at the position is the characteristic absorption peak of -CHO in 2,4,6-triformylpyrogallol. After the polymerization reaction, the disappearance of the characteristic absorption peaks of -NH2 and -CHO of the corresponding monomers proves that the polymerization reaction is very thorough;

[0050] Fig.12 As shown, it is the infrared spectrum of TPCOF-CF3 synthesized in 12M acetic acid of the present invention (curve 1 is TPCOF-CF3-20; curve 2 is TPCOF-CF3-19; curve 3 is TPCOF-CF3-18; curve 4 is TPCOF-CF3-17; curve 5 is TPCOF-CF3-16; curve 6 is 2,5-diaminotrifluorotoluene; curve 7 is 2,4,6-triformylpyrogallol). At 3100-3500cm -1 The peak at position is the characteristic absorption peak of -NH2 in 2,5-diaminotrifluorotoluene, 1642 cm -1The peak at the position is the characteristic absorption peak of -CHO in 2,4,6-triformylpyrogallol. After the polymerization reaction, the disappearance of the characteristic absorption peaks of -NH2 and -CHO of the corresponding monomers proves that the polymerization reaction is very thorough;

[0051] Fig.13 The figure shows the powder diffraction spectrum of TPCOF-CF3-8, corresponding to Example 1. There is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material;

[0052] Fig.14 Shown is the thermogravimetric diagram of TPCOF-CF3-8, corresponding to Example 1. The thermal decomposition temperature shown by thermogravimetric analysis exceeds 500°C, indicating that it has high thermal stability;

[0053] Fig.15 The figure shows the nitrogen adsorption-desorption of TPCOF-CF3-8, corresponding to Example 1. The BET specific surface area of ​​TPCOF-CF3-8 is 825 m 2 g -1 ;

[0054] Fig.16 As shown, it is the pore size distribution diagram of TPCOF-CF3-8, corresponding to Example 1. The main pore size of TPCOF-CF3-8 material is at 1.5 nm;

[0055] Fig.17 Shown is a scanning electron microscope image of TPCOF-CF3-8, corresponding to Example 1. Most of TPCOF-CF3-8 is fibrous;

[0056] Fig.18 The figure shows the carbon NMR spectrum of TPCOF-CF3-8, corresponding to Example 1. The literature reports that the -CHO carbon peak in 2,4,6-triformylphloroglucinol is located at 190ppm, while there is no carbon peak at 190ppm in TPCOF-CF3-8, which indicates that the aldehyde group in the monomer has been completely reacted. 154.4ppm is the carbon peak of the enamine bond (CN bond) in the TPCOF-CF3-8 skeleton, and 185.0ppm is the carbon peak of the keto carbonyl (C=O bond) after structural tautomerism. The carbon NMR spectrum shows that the target structure product is obtained;

[0057] Fig.19 The adsorption isotherms of CH4, C2H6 and C3H8 for TPCOF-CF3-8 at 298K are shown, corresponding to Example 1. At 1 bar, the adsorption amounts of CH4, C2H6 and C3H8 are 4.8, 30 and 63 cm 3 g -1 ;

[0058] Fig. 20The adsorption isotherms of CH4, C2H6 and C3H8 for TPCOF-CF3-8 at 273K are shown, corresponding to Example 1. At 1 bar, the adsorption amounts of CH4, C2H6 and C3H8 are 6.5, 46 and 75 cm 3 g -1 ;

[0059] Fig.21 As shown, the separation ratio (calculated using IAST) curve of propane / methane (curve 1) and ethane / methane (curve 2) of TPCOF-CF3-8 at 298K, corresponding to Example 1. At 100 kPa, the separation ratios of propane / methane (curve 1) and ethane / methane (curve 2) are 346.3 and 13.5, respectively;

[0060] Fig. 22 As shown, the separation ratio (calculated using IAST) curve of propane / methane (curve 1) and ethane / methane (curve 2) of TPCOF-CF3-8 at 273K, corresponding to Example 1. At 100 kPa, the separation ratios of propane / methane (curve 1) and ethane / methane (curve 2) are 5016 and 38.8, respectively;

[0061] Fig.23 The figure shows the powder diffraction spectrum of TPCOF-CF3-19, corresponding to Example 2. There is an obvious diffraction peak at about 5°, which proves that the polymer has good crystallinity and is a long-range ordered crystalline porous material;

[0062] Fig.24 The figure shows the nitrogen adsorption-desorption of TPCOF-CF3-19, corresponding to Example 2. The BET specific surface area of ​​TPCOF-CF3-19 is 740 m 2 g -1 ;

[0063] Fig.25 The figure shows the pore size distribution of TPCOF-CF3-19, corresponding to Example 2. The main pore size of the TPCOF-CF3-19 material is at 1.55 nm. DETAILED DESCRIPTION

[0064] Embodiments 1 to 21:

[0065] Weigh 2,4,6-triformylpyrogallol (TP, 42 mg, 0.2 mmol) and 2,5-diaminotrifluorotoluene (TFBA, 52.8 mg, 0.3 mmol) and add them to a 10 mL ampoule; then add n-butanol and o-dichlorobenzene (1 mL / 1 mL); ultrasonicate the reaction solution for 60 minutes to ensure that the solution is evenly mixed; add 0.3 mL of 6M acetic acid (HAC) solution to the above solution and let it stand for 30 minutes; perform a "freeze-vacuum-thaw" cycle operation 4 times under liquid nitrogen and argon atmosphere, and then seal the ampoule under vacuum; react at 120°C for 3 days; the ampoule is slowly opened after cooling to room temperature. Vacuum filter to obtain a solid, wash with anhydrous tetrahydrofuran and soak for 1 day, and change the solvent every 8 hours. Finally, the solid is vacuum dried at 100°C for 12 hours to obtain a wine red powder, which is the TPCOF-CF3-8 (94%) described in the present invention.

[0066] Weigh 2,4,6-triformylpyrogallol (TP, 42 mg, 0.2 mmol) and 2,5-diaminotrifluorotoluene (TFBA, 52.8 mg, 0.3 mmol) and add them to a 10 mL ampoule; then add n-butanol and o-dichlorobenzene (1 mL / 1 mL); ultrasonicate the reaction solution for 60 minutes to ensure that the solution is evenly mixed; add 0.4 mL of 12 M acetic acid (HAC) solution to the above solution and let it stand for 30 minutes; perform a "freeze-vacuum-thaw" cycle operation 4 times under liquid nitrogen and argon atmosphere, and then seal the ampoule under vacuum; react at 120°C for 3 days; the ampoule is slowly opened after cooling to room temperature. Vacuum filter to obtain a solid, wash with anhydrous tetrahydrofuran and soak for 1 day, and change the solvent every 8 hours. Finally, the solid is vacuum dried at 100°C for 12 hours to obtain a wine red powder, which is the TPCOF-CF3-19 (92%) described in the present invention.

[0067] By changing the concentration and amount of acetic acid, the concentrations of acetic acid were 3M, 6M, 9M and 12M, and the volumes were 0.1mL, 0.2mL, 0.3mL, 0.4mL and 0.5mL, respectively. The other conditions remained unchanged, and the corresponding numbers of the products obtained were TPCOF-CF3-1 to TPCOF-CF3-20, as shown in Table 1. X-ray powder diffraction results show that TPCOF-CF3-8 has high crystallinity.

[0068] Table 1: Products obtained with different acetic acid concentrations (M) and volume dosages (mL)

[0069]

[0070] The binary mixed solvent "n-butanol and o-dichlorobenzene (1 mL / 1 mL)" in the preparation of TPCOF-CF3-8 was replaced with "1,4-dioxane and mesitylene (1 mL / 1 mL)", and other conditions remained unchanged to obtain the product TPCOF-CF3-21. The X-ray powder diffraction results showed that TPCOF-CF3-8 had high crystallinity, as shown in Table 2.

[0071] Table 2: Products obtained using different binary mixed solvents

[0072]

[0073] The activation solvent ultra-dry tetrahydrofuran in the preparation of TPCOF-CF3-8 was replaced with anhydrous acetone and anhydrous methanol, and the other conditions remained unchanged to obtain the product. The X-ray powder diffraction results showed that TPCOF-CF3-8 had high crystallinity, as shown in Table 3.

[0074] Table 3: Products obtained using different activation solvents

[0075]

[0076] Embodiments 22 to 29:

[0077] The volume ratio of the binary mixed solvent n-butanol and o-dichlorobenzene used to prepare TPCOF-CF3-8 in Example 1 was modified to 1:5, 1:4, 1:3, 1:2, 2:1, 3:1, 4:1 and 5:1, respectively, to obtain products TPCOF-CF3-22 to TPCOF-CF3-29. X-ray powder diffraction results show that TPCOF-CF3-8 has high crystallinity.

[0078] Table 4: Products obtained by different volume ratios of o-dichlorobenzene and n-butanol

[0079]

[0080] In summary, the present invention uses 2,5-diaminotrifluorotoluene and 2,4,6-triformylpyrogallol as monomers and acetic acid as a catalyst to synthesize TPC0F-CF3, which are numbered as TPC0F-CF3-1 to TPC0F-CF3-29. The effect of synthesis conditions on the crystallinity of the product was studied in detail using X-ray powder diffraction. Thermogravimetric analysis shows that the thermal decomposition temperature of TPC0F-CF3-8 exceeds 500°C, and it has high stability. The nitrogen adsorption-desorption curve of TPC0F-CF3-8 was tested, and its BET specific surface area was calculated to be 825m 2 g -1 ; In addition, the adsorption properties of methane, ethane and propane of TPCOF-CF3-8 were studied in detail at 273K and 298K.

[0081] As described above, for those skilled in the art, various other corresponding changes and modifications can be made based on the technical solutions and technical concepts of the present invention, and all these changes and modifications belong to the protection scope required by the present invention.

Claims

1. A method for preparing a covalent organic framework material containing trifluoromethyl groups in its pores, comprising the following steps: (1) Weighing 0.2 mmol of 2,4,6-triformylpyrogallol and 0.3 mmol of 2,5-diaminotrifluorotoluene into a reaction container, and then adding a two-component mixed solvent with a total volume of 2 mL, and ultrasonicating for 50 to 70 minutes to ensure that the solution is evenly mixed; the two-component mixed solvent is a mixture of o-dichlorobenzene and n-butanol or 1,4-dioxane and mesitylene; (2) adding 0.1 to 0.5 mL of 3 to 12 M acetic acid solution to the solution obtained in step (1), allowing to stand for 20 to 40 minutes, and then performing a "freeze-vacuum-thaw" cycle operation 2 to 5 times in a liquid nitrogen and argon atmosphere, with the freezing temperature being 77 K, and thawing to room temperature; then sealing the reaction vessel under vacuum and reacting at 110 to 130°C for 60 to 80 hours; (3) After cooling the reaction vessel of step (2) to room temperature, slowly open it and vacuum filter to obtain a solid; wash the obtained solid with an anhydrous solvent and soak it for 20 to 30 hours, during which the solvent is changed every 6 to 8 hours; finally, vacuum dry the obtained solid at 90 to 110° C. for 10 to 15 hours, thereby obtaining a pore-containing trifluoromethyl covalent organic framework material with the structural formula shown below; 2. The method for preparing a covalent organic framework material containing trifluoromethyl groups in pores according to claim 1, characterized in that: In step (1), the volume ratio of o-dichlorobenzene to n-butanol or 1,4-dioxane to mesitylene is 1:0.2-5.

3. The method for preparing a covalent organic framework material containing trifluoromethyl groups in pores according to claim 1, characterized in that: In step (3), the anhydrous solvent is ultra-dry tetrahydrofuran, anhydrous acetone or anhydrous methanol.

4. Use of a covalent organic framework material containing trifluoromethyl groups in its pores prepared by the preparation method according to any one of claims 1 to 3 in the adsorption and separation of methane, ethane or propane.

Citation Information

Patent Citations

  • Preparation method and application of halogen-modified covalent organic framework material

    CN115124676A

  • Preparation method and application of trifluoromethyl-modified covalent organic framework material

    CN115490823A